32 Contraception: use and understanding in women with adult congenital heart disease. (2nd February 2018) - Lynn, P; Simpson, M; Jansz, S; Muirhead, E; Mearns, J; Uribe-Morales, I; Walker, N
Abstract : Purpose: Successes in care of congenital heart disease (CHD) have resulted in an increasing number of our patients considering pregnancy. For some, pregnancy could be a significant undertaking. We believe that we counsel our patients about contraception. Our aim was to assess contraception advice from a patient's perspective. Methods: An audit questionnaire was designed and given to women of child-bearing age attending the Scottish Adult Congenital Cardiology outpatient clinic. Results: 20 questionnaires were returned (mean age: 27 years). 17 (85%) were currently sexually active, 2 (10%) declined to comment. Contraceptive methods frequency is demonstrated in the table below: 17 (85%) were either unsure or not actively planning a pregnancy. 8 (40%) were unsure if their current medications were safe to continue if they were to become pregnant. 6 (30%) had previously been informed pregnancy was not advisable and all were using some form of contraception. GPs were the most common source of contraceptive information (n=10 [50%]). Only 9 (45%) recalled receiving contraceptive advice from our team. 19 (95%) thought specific information on contraception for women with CHD would be useful. Conclusion: Compared with our audit completed in 2011 there was an increased retention of contraceptive advice. For further improvement, we have developed more accessible information about safe and effective methods of contraception for adults with CHD and will repeat the audit.